Clave de fa: creación y realización audiovisual de sesiones acústicas en vivo de artistas o proyectos musicales femeninos - Caceres Espejo, Rodrigo Humberto (2022)
This paper recounts the creation of "Clave de Fa", a feminist musical project for the platform Youtube, which consists on the production and broadcasting of acoustic musical sessions by female artists or female-led musical projects. The project aims to create a safe space for musical expression that provides female artists with visibility and empowerment. All this while delivering a quality audiovisual product that manages to connect with the audience through its content, cinematography and art. Thus contributing, through production and audiovisual communication, to reduce the gender gap by showcasing female artists in the Peruvian music scene